The Dosage of the Derivative of Clostridium Ghonii (DCG) Spores Dictates Whether an IFNγ/IL-9 or a Strong IFNγ Response Is Elicited in TC-1 Tumour Bearing Mice. (28th April 2019) - Ni, Guoying; Wang, Yong; Good, David; Yuan, Jianwei; Pan, Xuan; Wei, Jou; Liu, Xiaosong; Wei, Ming Q.
Abstract : Background . Anaerobic Clostridial spores (CG) cause significant oncolysis in hypoxic tumour microenvironment and result in tumour regression in both animal models and clinical trials. The immune mediated response plays a critical role in the antitumour effect by the anaerobic spore treatment. Method . Human papillomavirus 16 E6/E7 transformed TC-1 tumour bearing mice were intravenously administered with low (1 × 10 8 CFU/kg) or high dosage (3 × 10 8 CFU/kg) of Derivative Clostridial spore (DCG). Results . Intravenous administration of the derivative of Clostridial ghonii (DCG) spores leads to both tumour and systemic inflammatory responses characterized by increased IFN γ /IL-9 secreting T cells in the spleen and the tumour. Low numbers of antigen specific T cells (<20/10 6 spleen cells) in the spleen of the tumour bearing mice are also detected after intravenous DCG delivery. Interestingly, our results showed that a mixed IL-9/IFN γ secreting T cell response was induced when the tumour bearing mice received a low dose of DCG spore (1 × 10 8 CFU/kg), while a strong IFN γ response was elicited with a high dosage of DCG spore (3 × 10 8 CFU/kg). Conclusion . The dosage of DCG spore will determine the types of the DCG induced immune responses.